Assimilating Seoul Japanese rule and the politics of public space in colonial Korea, 1910-1945 (Asia Pacific modern, 2014)
"Assimilating Seoul, the first English-language book-length study of colonial Seoul during the years 1910-1945, challenges conventional nationalist paradigms to reveal the intersection of Korean and Japanese history in this important capital. Henry offers a transnational account that treats the city's public spaces as "contact zones." Through micro-histories of Shinto festivals, industrial expositions, and sanitation campaigns, he shows how residents negotiated pressures to become loyal, industrious, and hygienic subjects of the Japanese empire. Unlike previous, top-down analyses, this ethnographic history investigates modalities of Japanese rule as experienced from below. Although the colonial state set ambitious goals for the integration of Koreans, Japanese settler elites and lower-class expatriates reshaped the speed and direction of assimilation by bending government initiatives to their own interests and identities. Meanwhile, Korean men and women of different classes and generations re-articulated the terms and degree of their incorporation into a multi-ethnic polity. Assimilating Seoul captures these fascinating responses to an empire that used the lure of empowerment to disguise the reality of alienation"--